Safe house - Espinosa, Daniel, 1977-; Stuber, Scott; Guggenheim, David; Washington, Denzel, 1954-; Reynolds, Ryan.; Farmiga, Vera.; Shepard, Sam, 1943-2017.; Gleeson, Brendan; Patrick, Robert, 1958-; Blades, Ruben; Arnezeder, Nora, 1988-; Relativity Media; et al. (Universal City, CA : Universal Studios Home Entertainment, 2012)
Tobin Frost, one of the CIA's most dangerous traitors, resurfaces in South Africa after eluding capture for almost a decade. During his interrogation, the safe house he's being held in is attacked by brutal mercenaries, forcing rookie agent Matt Weston to take the infamous Frost on the run. As the masterful manipulator toys with his reluctant protege, shaking the young operative's morality and idealism, the unlikely allies must fight to stay alive long enough to uncover who wants them dead.
Title from container.
Originally released as a motion picture in 2012.
Release date: Jun. 5, 2012.
Bonus materials: Making-of ; hand-to-hand action ; shooting the safe house attack ; building the rooftop chase ; behind the action ; inside the CIA ; Safe harbor: Cape Town.
Director of photography, Oliver Wood ; editor, Richard Pearson ; music, Ramin Djwadi.
Denzel Washington, Ryan Reynolds, Vera Farmiga, Brendan Gleeson, Sam Shepard, Ruben Blades, Nora Arnezeder, Robert Patrick.
Keywords: United States -- Central Intelligence Agency -- Drama; Traitors -- Drama; Action and adventure films; Drama; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired